Normal electrocardiographic findings: recognising physiological adaptations in athletes - Drezner, J. A.; Fischbach, P.; Froelicher, V.; Marek, J.; Pelliccia, A.; Prutkin, J. M.; Schmied, C. M.; Sharma, S.; Wilson, M. G.; Ackerman, M. J.; Anderson, J.; Ashley, E.; et al. (British Journal of Sports Medicine, 2013)
Electrocardiographic changes in athletes are common and usually reflect benign structural and electrical remodelling of the heart as a physiological adaptation to regular and sustained physical training (athlete's heart). The ability to identify an abnormality on the 12-lead ECG, suggestive of underlying cardiac disease associated with sudden cardiac death (SCD), is based on a sound working knowledge of the normal ECG characteristics within the athletic population. This document will assist physicians in identifying normal ECG patterns commonly found in athletes. The ECG findings presented as normal in athletes were established by an international consensus panel of experts in sports cardiology and sports medicine.